Antioxidant activity test of ethanol extract of red algae (Kappaphycus alvarezii) green variety from north coasts of Jepara district with DPPH method - Wulandari Wulandari; Arifah Irna Nur Widyastuti; Ahmad Fuad Masduqi (Journal of Health Management and Pharmacy Exploration, 2023)
Free radicals are unstable and highly reactive molecules that can cause cells damage. This cell damage can be inhibited by antioxidant compounds. One of the red algae, Kappaphycus alvarezii, is thought to contain phenolics and flavonoids compounds that can b used US antioxidants compounds. this study aims to determine the ethanol extract of red algae (Kappaphycus alvarezii) green variety has antioxidants activity using the DPPH method. this study also aims to determine the IC 50 value of the ethanolic extract of red algae (Kappaphycus alvarezii) green variety. The antioxidant activity test of red algae ethanol extract was carried out using the DPPH method. The results showed that the ethanolic extract of red algae (Kappaphycus alvarezii) green variety had antioxidant activity and the IC 50 value of the ethanolic extract of red algae was 242.28 ppm with a very weakcategory.